Aplicação tópica de ácido tranexâmico em pacientes anticoagulados submetidos à cirurgia oral menor : revisão sistemática e meta-análise - Vasconcellos, Sara Juliana de Abreu de (2015)
Oral anticoagulants are widely used for primary prevention of thromboembolic events in patients with atrial fibrillation and prosthetic heart valves. The treatment of patients under OAT who need oral surgery procedures is varied and controversial due to the discussion on the uncontrolled bleeding and the possibility of thromboembolic complications. Currently, intravenous tranexamic acid (TXA) has been proven to be effective in preventing bleeding in several types of surgery, including orthognathic surgery. To the best of our knowledge, there is no evidence on the efficacy and safety of topical TXA in reducing blood loss in anticoagulated patients undergoing minor oral surgery procedures. The aim of this systematic review with meta-analysis is to investigate the efficacy and safety of topical TXA to prevent postoperative bleeding in anticoagulated patients undergoing minor oral surgery. A systematic search in PubMed, SCOPUS, Cochrane Central Register of Controlled Trials (CENTRAL), OpenThesis and international database for clinical trials from inception to May 2015 was done. A grey-literature search was conducted through Google Scholar. Our search was restricted to studies published in full-text versions, without language restriction. Two reviewers independently screened the search results and identified clinical trials that compared the use of topical TXA versus other topical hemostatic agent, placebo or interruption/decrease of anticoagulant therapy prior to the surgery. Our predefined outcomes were bleeding within the first postoperative week with need for clinical intervention and thromboembolic events. The risk of bias was assessed according to the Cochrane guidelines for clinical trials. The pooled relative risk (RR) was calculated for the effect of topical application of TXA on postsurgical bleeding. Statistical heterogeneity was assessed using the Cochran Q test and quantified by the I2 index. To assess potential publication bias we created a funnel plot by plotting the individual estimates in log units against the standard error. After screening titles and abstracts, 21 full-text articles were assessed for eligibility and 7 clinical trials were included in the final analysis (a total of 533 patients). The combined RR for the number of patients receiving TXA in comparison to the control group was 0.42 (95% CI 0.21 to 0.84; p = 0.01), indicating a protective effect of topical TXA on bleeding after minor oral surgeries. A moderate between-study heterogeneity was observed (I2 = 26%) that disappeared (I2 = 0%) after subgroup analysis by different strategies used in the control groups. Subgroup analysis revealed that topical TXA was effective to prevent postsurgical bleeding compared to placebo (RR = 0.09; 95% CI 0.02 to 0.48; p = 0.004) and epsilon-aminocaproic acid (RR = 0.12; 95% CI 0.01 to 0.94; p = 0.04). However, no significant difference was observed in other analysis. There were no cases of thromboembolic events in any study, in either the TXA or the control groups, during the one to 7 day follow-up period after surgery. Available data suggest that irrigation of surgical site with TXA followed by mouthwash during the first postoperative week can reduce the risk of bleeding after minor oral surgeries in anticoagulated patients. However, additional trials should be conducted to compare TXA efficacy over absorbable hemostatic materials.